Microbiomes: unifying animal and plant systems through the lens of community ecology theory - Christian, Natalie; Whitaker, Briana K.; Clay, Keith (Frontiers in Microbiology, 2015)
The field of microbiome research is arguably one of the fastest growing in biology. Bacteria feature prominently in studies on animal health, but fungi appear to be the more prominent functional symbionts for plants. Despite the similarities in the ecological organization and evolutionary importance of animal-bacterial and plant-fungal microbiomes, there is a general failure across disciplines to integrate the advances made in each system. Researchers studying bacterial symbionts in animals benefit from greater access to efficient sequencing pipelines and taxonomic reference databases, perhaps due to high medical and veterinary interest. However, researchers studying plant-fungal symbionts benefit from the relative tractability of fungi under laboratory conditions and ease of cultivation. Thus each system has strengths to offer, but both suffer from the lack of a common conceptual framework. We argue that community ecology best illuminates complex species interactions across space and time. In this synthesis we compare and contrast the animal-bacterial and plant-fungal microbiomes using six core theories in community ecology (i.e., succession, community assembly, metacommunities, multi-trophic interactions, disturbance, restoration). The examples and questions raised are meant to spark discussion amongst biologists and lead to the integration of these two systems, as well as more informative, manipulatory experiments on microbiomes research.